Extent of Prescribing Antibiotics And Corticosteroids on COVID-19 Admitted Patients Into a Corona Dedicated Hospital In Khulna - Islam, Baishakhi; Bhuiyan, Mohammad Monzurul Alam; Yesmin, Mst Shaila; Islam, Raihana; Rahman, Tasnim; Khanam, Mahfuja; Akhter, Shamima; Jannat, Tamanna (Journal of Dhaka Medical College, 2023)
Background: Majority of the patients infected with SARS-CoV-2 receive antibiotics and corticosteroids though its role has not yet been adequately defined. Inappropriate use of antibiotics despite bacterial co-infections may lead to global antibiotic resistance. Aim and objectives: We aim to assess the using pattern of antibiotics and corticosteroids in different clinical categories of COVID-19 patients admitted to a hospital. Materials and methods: This is a cross sectional study where 345 clinically diagnosed COVID 19 patients having coexisting diseases of both sexes with different age group received antibiotics and corticosteroids were included. Patients’ demographic profile, treatment plan were obtained using a specially designed form. All data were compiled in Microsoft excel spreadsheet and results expressed in total number and percentage. Results: Out of total 345 patients, male (53.62%) and female patients (46.37%) of age group between 41 to 60 years (42.89%) of different categories; mild (28.40%), moderate ((39.42%), severe (24.63%), critical (7.53%) cases were enrolled in this study. Moxifloxacin followed by ceftriaxon was most commonly prescribed antibiotic in all clinical groups with higher percentages. Other antibiotic includes meropenem, amoxicillin+ clavulanic acid, piperacillin+tazobactam, linezolid also prescribed in higher rate. Among systemic corticosteroids, dexamethasone followed by methylprednisolone, hydrocortisone was prescribed invariably with higher percentages. Conclusion: With the rapid increase in the rate of infection, purposeful use of antibiotic and corticosteroid might be considered as a better treatment option to fight against COVID 19 patients. J Dhaka Med Coll. 2021; 30(2) : 149-155